Design, Synthesis, and Antifungal Analysis of Pyrazoline Derivatives Against Candida Species: A Comprehensive In Vitro and In Silico Approach - Rohim, Muhammad; Haryani, Yuli; Frimayanti, Neni; Muttaqin, Fauzan Zein; Teruna, Hilwan Yuda; Hendra, Rudi (Indonesian Journal of Chemistry, 2025)
This study utilized in vitro and in silico methods to assess the antifungal efficacy of synthesized pyrazoline derivatives (4a–e) against Candida species. The compounds were produced by a one-pot process and structurally analyzed using spectroscopic methods. The antifungal efficacy was evaluated against C. albicans, C. glabrata, and C. krusei using minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) assays. Among the derivatives, compound 4e exhibited potent antifungal action, displaying MIC values similar to ketoconazole. Molecular docking and pharmacophore modeling have shown that 4e interacts efficiently with critical residues of lanosterol 14α-demethylase (CYP51). The density functional theory (DFT) study indicated advantageous electrical characteristics, while molecular dynamics simulations validated the structural stability of the 4e–CYP51 complex, evidenced by low RMSD and RMSF values, along with an MM/GBSA binding energy comparable to that of ketoconazole. A robust association between binding energy and MIC substantiates the predictive use of computational data. The results suggest that compound 4e replicates the binding characteristics of ketoconazole and may be a viable candidate for antifungal medication development. This integrative strategy reinforces the justification for additional optimization and preclinical assessment of pyrazoline-based antifungal drugs aimed at CYP51.